Market fundamentalism in the age of 'haute finance': The enclosing of policy space in 'emerging' India - Lakshminarayan, Srivatsan (Ephemera: Theory & Politics in Organization, 2017)
The rise of the Emerging Market is a remarkable exemplar of an idea that originated and was socialized in Western financial markets during the 1980s. It has since gained rapid, wider normative status with respect to a particular set of beliefs that motivate policy choices on macroeconomic management, economic development and financial sector reforms in developing and less developed countries. I draw on the Polanyian notion of commodification and recent extensions to his scholarship in the realm of ideas that seek to explicate processes through which the dominant ideal of the self-regulating market is justified as fundamental to the organization of society. Against the backdrop of globally mobile capital, I critique the prevalence of a particular ideology of emergence in which commodified geography and commodified finance interact to shape policy. In this process, evaluative talk plays a key role in legitimizing the expectations of global capital and overcoming inherent contradictions through the rhetoric of non-crises. I thus highlight the ascendance of a narrow and instrumentally economic understanding of emergence in contemporary, post reform India as is asserted in conventional policy discourse. I conclude by remarking on the significant constriction of ideational space for the consideration of alternative, historically informed approaches to social and economic development. The legacy of Karl Polanyi serves as a prophetic reminder for the consequences of such constriction.
Keywords: India; commodification; economic development; emerging markets; haute finance; macroeconomics